2023
DOI: 10.3390/buildings13102597
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Behavior of Reinforced Concrete Beams Made with Locally Produced Recycled Aggregate in the UAE

Abdullah M. Sagheer,
Sami W. Tabsh,
Sherif Yehia

Abstract: In this study, the feasibility of utilizing locally produced coarse recycled aggregate (RA) from demolition waste in the UAE for structural applications was investigated. A comprehensive literature review on the subject showed that the shear and flexural responses of reinforced beams utilizing aggregate from concrete demolition waste are greatly dependent on the aggregate replacement ratio and the quality of the recycled aggregate. The experimental program in this study consisted of three phases. Phase I focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…The experimental test results demonstrate that the tensile strength of pervious concrete drops from 1.56 MPa when natural aggregate is used to 0.67 MPa when recycled aggregate is used. Although concrete employing recycled aggregate is expected to be weaker in tension when compared with concrete containing natural aggregate, the observed drop is much more drastic when compared with previous studies by the authors [56][57][58][59][60][61] on non-pervious concrete. The inferior quality of the recycled coarse aggregate due to its higher water absorption, lower density, possible content of organic substances, higher level of crushability, and reduced abrasion resistance contributes to lower tensile strength of pervious concrete.…”
Section: Split Tensile Strengthcontrasting
confidence: 56%
See 1 more Smart Citation
“…The experimental test results demonstrate that the tensile strength of pervious concrete drops from 1.56 MPa when natural aggregate is used to 0.67 MPa when recycled aggregate is used. Although concrete employing recycled aggregate is expected to be weaker in tension when compared with concrete containing natural aggregate, the observed drop is much more drastic when compared with previous studies by the authors [56][57][58][59][60][61] on non-pervious concrete. The inferior quality of the recycled coarse aggregate due to its higher water absorption, lower density, possible content of organic substances, higher level of crushability, and reduced abrasion resistance contributes to lower tensile strength of pervious concrete.…”
Section: Split Tensile Strengthcontrasting
confidence: 56%
“…The tests showed that 100% replacement of the aggregate caused the compressive strength of pervious concrete to reduce by 36%, from 7.08 to 4.53 MPa. Earlier studies by the first two authors [56][57][58][59][60][61] on non-pervious concrete have indicated the full replacement of natural coarse aggregate with recycled aggregate from construction demolition waste obtained from the same source can reduce the compressive strength by an average of just 10-15%. The lack of adequate amount of fine aggregate in pervious concrete increases the importance of the coarse aggregates and the bond between them to the mechanical properties of the concrete.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…A.M. Sagheer studied the feasibility of utilizing locally produced coarse recycled aggregate (RA) from demolition waste in the UAE for structural applications. Comprehensive reviews are presented in [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%